A way forward for design and analysis of neuroimaging studies of memory consolidation. Issue 3 (2nd October 2022) - Tallman, Catherine W.; Clark, Robert E.; Smith, Christine N.
ABSTRACT: Several novel ideas and suggestions were made in response to our discussion paper (Tallman et al., this issue). Careful consideration of the content and context of memory while accounting for the neuroanatomy and functional specialization of the hippocampus may reveal more consistent patterns in fMRI studies of memory consolidation. Below we address these ideas as well as issues that arise when interpreting the fMRI signal in memory consolidation studies. In addition, we describe new analyses suggested by the commentators that clarify our findings with respect to current theories.